Construction of a video about condom use for deaf and hearing people - Aline Cruz Esmeraldo Áfio; Sarah de Sá Leite; António Luís Rodrigues Faria de Carvalho; Paulo César de Almeida; Cristiana Brasil de Almeida Rebouças; Lorita Marlena Freitag Pagliuca (Rev Rene, 2021)
Objective: to build assistive technology, in video format, for deaf and hearing people about sexual health and condom use. Methods: methodological study consisting of the stages of pre-production, production and post-production. In pre-production we built the script, storyboard and scenes, following the principles of Lev Semenovich Vygotsky’s Theory of Learning. In production there was the development of the animation and recording of the scenes by the Libras interpreter. In post-production the final editing of the video took place. Results: the video “Condom: learn to use correctly”,lasting nine minutes and 25 seconds discusses the sexual and reproductive system of man and woman; mode of action, benefits and care with the use of condoms.Given the scarcity of educational materials on the subject, accessibility resources were used to build a video for deaf and hearing people. Conclusion: the construction of the video as an assistive technology directed to the deaf was successfully accomplished.